P186 Impact of tofacitinib maintenance therapy on key Ulcerative Colitis patient-reported outcomes of fatigue, urgency, abdominal pain and sexual dysfunction using IBDQ and SF-36 individual items as proxies. (30th January 2023) - Dubinsky, M C; Gardiner, S; Hur, P; Guo, X; Paulissen, J; Cappelleri, J C; Bushmakin, A G; Panés, J
Abstract: Background: Tofacitinib is an oral small molecule Janus kinase inhibitor for the treatment of ulcerative colitis (UC). This novel analysis evaluated tofacitinib outcomes using items from the Inflammatory Bowel Disease Questionnaire-32 (IBDQ) and Short Form-36 Health Survey (SF-36) as proxies for key UC patient-reported outcomes (PROs) of fatigue, urgency, abdominal pain and sexual dysfunction over 52 weeks of maintenance treatment. Methods: Data from 593 patients with UC in OCTAVE Sustain (NCT01458574) were included. 1 PROs were assessed via self-reported proxy items for each UC symptom/dysfunction of interest in the IBDQ and SF-36. A longitudinal mixed-effects model compared tofacitinib 5 and 10 mg twice daily (BID) vs placebo up to 52 weeks for change from baseline (CFB) in each predefined IBDQ and SF-36 item. Least squares (LS) mean differences and standardised effect sizes (ES; LS mean difference divided by the standard deviation [SD] of baseline item scores) were calculated for tofacitinib vs placebo; ES of 0.1, 0.2, 0.5 and 0.8 were trivial, small, medium and large, respectively, with ES categorisation intervals defined as the midpoints between these absolute values. 2 LS means and ES (LS mean/SD of baseline item scores) for both tofacitinib doses and placebo at Week 52 vs baseline were calculated. p<0.05 denoted statistical significance. Results: At Week 52, all IBDQ proxies were improved with tofacitinib 5 and 10 mg BID vs placebo, with significant LS mean differences. Large ES were reported for fatigue and urgency proxies; abdominal pain and sexual dysfunction proxies had medium ES (Figure 1). For SF-36 proxy items, LS mean differences vs placebo were significant at Week 52, except for the SF-36 fatigue proxies, 'Did you feel worn out?' and 'Did you feel tired?' (both 5 and 10 mg BID). Small to large ES were reported for fatigue proxies; the abdominal pain proxy had medium to large ES (Figure 2). Regarding CFB, tofacitinib 5 and 10 mg BID maintained responses in IBDQ and SF-36 proxies at Week 52. LS mean changes from baseline in IBDQ items were generally not significant with tofacitinib; this was not as evident for SF-36 items. Trivial to small ES were reported for tofacitinib 5 and 10 mg BID, and medium to large ES for placebo. Significant worsening was observed with placebo for all items of interest. Conclusion: Compared with placebo, tofacitinib 5 and 10 mg BID had better IBDQ and SF-36 proxy item responses at Week 52, as reflected through ES. Responses were maintained over 52 weeks with tofacitinib therapy but worsened with placebo. Proxy items have not been validated to measure the symptom PROs of interest. 1. Sandborn WJ et al. N Engl J Med 2017;376:1723–1736. 2. Dubinsky MC et al. Inflamm Bowel Dis 2021;27:983–993.